Pengaruh Inflasi, Kurs Rupiah Terhadap Dolar, Dan BI Rate, Terhadap Indeks Saham Syariah Jakarta Islamic Index(JII) Di Bursa Efek Indonesia(Periode Pengamatan 2010-2015) - Qodri, Hajad Rohman Al; , M. Sholahuddin, SE., M.Si (2015)
This research investigates the impact of inflation, the exchange rate, and interest rate (BI Rate) on Sharia stock index Jakarta Islamic Index in Indonesia Stock Exchange. The period of this study has been taken from January, 2010 to June, 2015 using time series on each other. The study used multiple linear regression method. The result showed that from each variable, inflation, the exchange rate and the interest rate, influence together (simultaneously) to Sharia stock index. It can be seen from the results of the data obtained F value of 41.484 with significant at 0.000 <0.05.Correlation between inflation and Sharia stock index was found to be positive but not significant. So that, the first hypothesis is not supported by research data. Further investigation found that the effect of exchange rate and Sharia stock index is positive and significant, so that the second hypothesis is supported by research data. While interest rate significantly give negative impact on sharia stock index, the third hypothesis is also supported by research data.The value of R Square in this study amounted to 0.667, so the coefficient at 66.7%. That means that the variable inflation, the exchange rate against the dollar and the BI rate can explain the effects on Sharia stock index by 66.7%, while the remaining 33.3% are explained by other factors not included in this study.Based on the result of this study, researcher wants that investor or the government is able to use risk management against the changes in domestic macroeconomic variables such as inflation, the exchange rate against the dollar, and the BI rate as resulted in this study.